Concordance of Patient‐Reported Joint Symptoms, Physician‐Examined Arthritic Signs, and Ultrasound‐Detected Synovitis in Rheumatoid Arthritis. Issue 6 (8th May 2017) - Hirata, Ayako; Ogura, Takehisa; Hayashi, Norihide; Takenaka, Sayaka; Ito, Hideki; Mizushina, Kennosuke; Fujisawa, Yuki; Yamashita, Naoko; Nakahashi, Sumie; Imamura, Munetsugu; Kujime, Rie; Kameda, Hideto
Abstract : Objective: Ultrasonography has been prevalently used as a valid and objective modality for joint examination in patients with rheumatoid arthritis (RA). This study aimed to examine and compare the concordance between ultrasound, clinical assessment, and patient‐reported assessment of joint synovitis in RA. Methods: Fifty patients with RA (84% female, median age 69 years, median disease duration 31 months, and median Disease Activity Score in 28 joints 3.8) completed the self‐evaluation of joint symptoms, including pain and considerable stiffness in the (proximal) interphalangeal, metacarpophalangeal, wrist, elbow, shoulder, knee, and ankle joints. These joints were also examined by a physician in order to assess the presence of tenderness or swelling; the presence of imaging synovitis was assessed by ultrasonography. Results: In a total of 1, 492 evaluated joints, symptoms (pain and stiffness), tenderness, and swelling were noted in 288 (19.3%), 182 (12.2%), and 220 (14.7%) joints, respectively, while ultrasound indicated synovitis in 317 (21.2%) joints. Overall concordance with ultrasound findings was lowest for joint tenderness (κ = 0.30), followed by symptoms (κ = 0.39), and by swelling (κ = 0.43), irrespective of the evaluated joint, except for the elbow. Moreover, the percentages of inflamed joints detected only on the basis of symptoms, tenderness, or swelling were 18.6%, 2.2%, and 8.5%, respectively, of all joints with signs of synovitis on ultrasonography. Conclusion: Joint swelling showed the best concordance with ultrasonography, followed by patient‐reported joint symptoms, and joint tenderness. Joint symptoms, rather than tenderness evaluation, may be a better clinical indicator of synovitis in RA patients.